A Study of Social Marketing Analysis for Business Intelligence and Applications in Context of Amazon Global Store (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Perhaps hardly anyone can claim that with the explosion of social media marketing in e-commerce, business intelligence has done anything better than promoting products for the Amazon global store more than it ever has before. This is a work-around on how social marketing analytics can help improve sales performance, customer engagement, and decision-making. His research employs such statistical tools as regression analysis, correlation tests, and approaches to forecasting and applying them, based on secondary data, to the impacts on the worldwide Amazon marketplace in 2019–2023 of the sentiment trends, product category growth, and social media ad success. The findings indicate that there is a tendency of increased customer satisfaction, of which positive consumer sentiment (2.72% every year, p < 0.001) and negative sentiment. Conversion rates and a CTR of 6.86% and thorough connection (r = 0.999) of a variety of it with conversion rates show that Instagram is the most successful marketing platform in t-commerce marketing. Moreover, the increase in the sales grew most with Fashion (CAGR 10.22), Electronics (CAGR 66.96), and Books deteriorated (CAGR -9.68), indicating that now the things consumers look up to first are the things that are digital first, which is an element of change. Such support was also present in hypothesis testing that customer experience would influence purchase behavior through the conversion rates (r = 0.991, p < 0.001, Positive sentiment). Sentiment-based pricing models and influencer marketing growth, among other things, report that Amazon can remain the king of e-commerce. These results also contribute to extending the field of digital commerce research and offer strategic implications on the use of social marketing tactics to obtain the most out of social marketing in the global e-commerce ecology.